2016
DOI: 10.21776/ub.jemis.2016.004.02.1
|View full text |Cite
|
Sign up to set email alerts
|

Pengukuran Dan Perbaikan Total Productive Maintenance (Tpm) Menggunakan Overall Equipment Effectiveness (Oee) Dan Root Cause Failure Analysis (Rcfa)

Abstract: Total productive Maintenance (TPM) is an initiative to optimize the effectiveness of manufacturing equipment which the objectives are elimination of all accidents, defects and downtimes [5]. The PendahuluanTantangan yang hadapi dalam suatu perusahaan adalah bagaimana meningkatkan produktivitas yang lebih tinggi dari proses produksinya. Untuk itu kelancaran proses produksi menjadi fokus utama dalam perusahaan karena terjadi kegiatan transformasi dari input menjadi output didalamnya. Salah satu faktor penduk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Kondisi persaingan pada sektor manufaktur saat ini semakin ketat, ini karena dalam perjalanan setiap tahunnya perkembangan pada sektor ini semakin meningkat pesat [1]. Dalam setiap bidang usaha atau perusahaan, peningkatan produktivitas dari proses yang dimiliki menjadi tantangan yang akan selalu dihadapi [2]. Termasuk pada bidang manufaktur yang banyak menggunakan mesin produktivitas menjadi sebuah tuntutan mutlak yang harus dipenuhi.…”
Section: Pendahuluanunclassified
“…Kondisi persaingan pada sektor manufaktur saat ini semakin ketat, ini karena dalam perjalanan setiap tahunnya perkembangan pada sektor ini semakin meningkat pesat [1]. Dalam setiap bidang usaha atau perusahaan, peningkatan produktivitas dari proses yang dimiliki menjadi tantangan yang akan selalu dihadapi [2]. Termasuk pada bidang manufaktur yang banyak menggunakan mesin produktivitas menjadi sebuah tuntutan mutlak yang harus dipenuhi.…”
Section: Pendahuluanunclassified
“…The results showed that the increase in OEE was due to proper machine utilization and reduced scrap in the process. (Amrussalam et al, 2016) Measurement and Repair of TPM in the Garment Industry…”
Section: Paper Summarymentioning
confidence: 99%
“…One of the success rates of the manufacturing industry is determined by the smoothness of the production process. [1] Said that increasing productivity in production is a challenge for companies. The smooth production process will be run well if the machine in the production process runs according to the planned schedule, but unfortunately, in the production process, downtime machine is often happening and make the production stop.…”
Section: Introductionmentioning
confidence: 99%